THE ROLE OF THE POLICE IN LAW ENFORCEMENT AGAINST PERPETRATORS CORRUPTION CRIMES THAT OCCURRED IN INDONESIA - Yogi Yahya Butar-Butar; Tajuddin Noor; Cut Nurita (Jurnal Ilmiah METADATA, 2025)
The police are authorized to investigate corruption crimes, but this authority is shared with the KPK and the Prosecutor's Office.. Law enforcement against perpetrators of corruption crimes that occur in the jurisdiction of the Serdang Bedagai I Resort Police is to conduct investigations into corruption cases that are not eligible to be investigated by the Corruption Eradication Commission. The Corruption Eradication Commission can only investigate corruption cases involving state apparatus and resulting in state financial losses of at least Rp.1,000,000,000.00 (one billion rupiah), for this reason the role of the prosecutor is needed as an investigator for corruption cases that are not eligible to be investigated by the Corruption Eradication Commission.